ANALYSIS OF HEAT WEATHER IN APRIL-MAY 2023 IN BANDUNG - Fathoni Averosyani, Muhammad
Recently, there has been a lot of media coverage regarding the heat weather conditions in Indonesia from April to May 2023. However, there is no clear information regarding how high these hot weather conditions are compared to usual conditions (climatology) and what causes them (mostly suspected). This study analyzes whether the hot weather reported in April-May 2023 in Bandung is the influence of the annual cycle or other phenomena. The data to be used in this study are air temperature (°C) and air humidity (%) data in the range of January in 2011 to May 2023 from the Official BMKG Cemara Station, Bandung. The location of the BMKG Cemara Station is at 107°59' N and - 6°88' E longitude. This data will be used to see the pattern of certain variables and the value of the comfort index (THI). The data that has been obtained will be analyzed to see variations in air temperature and air humidity. Then the data is processed through the THI method. The results of this study indicate that the heat weather that occurred in April and May 2023 in Bandung was not caused by the annual cyclone, but was caused by other phenomena. Because there were 24 days where the maximum temperature in April 2023 exceeded the climatological average for April 2011-2020. While in May there are 28 days where the maximum temperature in May 2023 exceeds the average climatology of May 2011-2020.